2016
DOI: 10.1016/j.bandl.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and gamma band oscillations index differential processing of acoustically reduced and full forms

Abstract: Reduced forms like yeshay for yesterday often occur in conversations. Previous behavioral research reported a processing advantage for full over reduced forms. The present study investigated whether this processing advantage is reflected in a modulation of alpha (8)(9)(10)(11)(12) Hz) and gamma (30+ Hz) band activity. In three electrophysiological experiments, participants listened to full and reduced forms in isolation (Experiment 1), sentence-final position (Experiment 2), or mid-sentence position (Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
0
16
2
Order By: Relevance
“…Studies on unimodal auditory degraded speech comprehension have demonstrated that parietal alpha power is enhanced when speech is degraded (Becker, Pefkou, Michel, & Hervais‐Adelman, ; Drijvers, Mulder, & Ernestus, ; Obleser & Weisz, ; Weisz, Hartmann, Müller, Lorenz, & Obleser, ; Wostmann, Herrmann, Wilsch, & Obleser, ). These results were interpreted as reflecting increased auditory cognitive load when the language processing system is inhibited due to degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on unimodal auditory degraded speech comprehension have demonstrated that parietal alpha power is enhanced when speech is degraded (Becker, Pefkou, Michel, & Hervais‐Adelman, ; Drijvers, Mulder, & Ernestus, ; Obleser & Weisz, ; Weisz, Hartmann, Müller, Lorenz, & Obleser, ; Wostmann, Herrmann, Wilsch, & Obleser, ). These results were interpreted as reflecting increased auditory cognitive load when the language processing system is inhibited due to degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to words that are lexically vowel-initial (e.g., align), variant vowel-initial word forms (e.g., [ d] for had) may show reduced or totally absent proximal acoustic discontinuities (e.g., glottalization or frication noise for /h/), which could otherwise serve as overt segmentation cues to the start of the word or presence of an extra syllable. The problem of how listeners recover representations under the highly variable pronunciations that occur in casual, everyday speech is a critically important and challenging problem in understanding the neurocognitive mechanisms of speech perception (Alexandrou, Saarinen, Kujala, & Salmelin, 2018;Drijvers, Mulder & Ernestus, 2016;Ernestus & Warner, 2011;Tucker & Ernestus, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The EEG data used for this paper was taken from [13,14]. In three passive listening experiments, right-handed native listeners of Dutch were instructed to listen attentively to the presented speech input and were told that they would get questions about the words and sentences they were about to hear.…”
Section: Description Of the Datamentioning
confidence: 99%
“…For the filler sentences, there was no specific instruction. The reduced and unreduced verb forms were spliced out of their original sentences and were pasted into the carrier sentence or presented in isolation (these were segmented from the sentences in which these targets occurred at sentence-final position; see [13,14] for more details). This was done to make sure that the reduced and unreduced sentences only differed with respect to the realization of the target verb form.…”
Section: Stimulus Materialsmentioning
confidence: 99%